Model rozwijania refl eksyjności u (przyszłych) nauczycieli edukacji wczesnoszkolnej – założenia, istota, motywy konstruowania i nadawania mu wymiaru praktycznego - Joanna Szymczak (Problemy Wczesnej Edukacji)
The aim of the article is to present an original model of developing refl exivity in reference to educational events. The Department of Didactics and Studies in the Culture of Education lends the model a practical dimension in working with early school education teachers-to-be during the Refl exive Teacher Workshops course. The inspiration for creating (and sustaining) the model is a carried out under the direction of prof. Ewa Filipiak, Ph.D and is a research project concerning refl ection in reference to educational events taken up by early school education teachers. The article indicates three concepts: (1) critical events in teaching by D. Tripp, (2) the refl exive practitioner by D.A. Schön and (3) mindfulness and mindlessness by E.J. Langer, all of which constitute a theoretical background for the model. The paper also presents an adopted understanding of refl exivity and refl ection. Moreover, the paper considers the motives for using the model while working with teachers-to-be. Therefore, it discusses the value of being and becoming a refl exive teacher, as well as characteristic features of a refl exive practitioner and their signifi cance for working with students.